Enabling Authentic Activities for Effective Collaboration in Remote Access Laboratories - Ali Habibi, Abdelnour Aldraho (Journal of Pure & Applied Sciences, 2020)
The online learning challenge is one of the most significant issues addressed and raised these days. Especially during the emergence of the Covid19 pandemic and the consequent changes in online learning, particularly the practical courses. This study indicates that to apply the traditional Doolittle Principles which has developed eleven principles to support collaboration in a face-to-face classroom, to online learning. The collaboration is an interactive process that engages two or more participants working together to achieve educational outcomes they could not accomplish independently. These principles will be used on the study in remote access laboratories by participating two or more participants in a remote laboratory experiment from different locations, where the remote laboratories can define as a class of online learning systems that provide access to laboratory infrastructure and learning environments through the Internet. This instructional guideline will be developed and trialled in order to address this aspect. As a result, Doolittle principles can be applied theoretically in the context of online learning activities to support the Remote Access Laboratories (RAL) activity.